(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
Vata Vyadhi encompasses a broad range of neuromuscular, musculoskeletal, and degenerative disorders caused by Vata Dosha vitiation, leading to symptoms such as pain, stiffness, and mobility impairment. This case study evaluates the impact of Ayurvedic interventions in managing Vata Vyadhi in a 60-year-old female patient who visited Jeena Sikho Lifecare Limited Hospital, Mathura, Uttar Pradesh, India. She presented with radiating lower limb pain, knee joint pain, and left-sided radiculopathy. The patient underwent Ayurvedic treatment, including dietary modifications, Ayurvedic formulations, and lifestyle management. Post-treatment, she experienced significant pain relief and improved mobility, with no recurrence of symptoms. Additionally, improved vital signs and laboratory parameters indicated a positive therapeutic response. From a modern perspective, VataVyadhi correlates with conditions like osteoarthritis, sciatica, and neuropathy, often diagnosed through MRI, CT scans, and inflammatory markers. While conventional medicine relies on analgesics, muscle relaxants, and surgery, Ayurvedic treatment offer a holistic approach addressing both symptoms and underlying pathology. This case highlights the potential efficacy of Ayurveda in Vata disorder management, though further clinical trials and standardized protocols are needed to validate these findings and integrate Ayurveda into mainstream healthcare.